Correlation of Gut Microbiota, Vitamin D Status, and Pulmonary Function Tests in Children With Cystic Fibrosis - Albedewi, Hadeel; Bindayel, Iman; Albarrag, Ahmed; Banjar, Hanaa (Frontiers in Nutrition, 2022)
Background: Children with cystic fibrosis (CF) are expected to have suboptimal serum vitamin D status and altered gut microbiota. The altered gut microbiota is hypothesized to have a pro-inflammatory effect that further complicates the existing respiratory inflammation. Emerging evidence suggests an association between vitamin D and gut microbiota. The aim of the study is to assess the relationships between 25-hydroxyvitamin D status, pulmonary function, and fecal bacteria in CF children. Methods: In this cross-sectional study, a total of 35 children with CF (8.7±2.83 years) and 24 controls without CF (9±2.7 years) were included in the study. Serum 25-hydroxyvitamin D 25(OH)D status was measured using Elecsys vitamin D total II assay. In the CF group, gut microbiota composition was assessed using real-time PCR analysis. Pulmonary function tests were measured using spirometry. Comparisons between the CF and non-CF control were conducted using independent samples t-test. In the CF group, one-way analysis of variance (ANOVA) was used to assess differences in pulmonary function tests and gut microbiota composition across the three vitamin D subgroups. The correlations between 25-hydroxyvitamin D status and pulmonary function tests, or gut microbiota composition, and pulmonary function tests with gut microbiota composition were analyzed using Pearson's correlation coefficient test. Results: Children with CF had significantly lower serum 25(OH)D levels compared to children without CF (44.3±22.4 vs 59±25.5, respectively, P=0.026). Children with CF with optimal serum 25(OH)D level had significantly higher levels of Bacteroidetes, Firmicutes, and total bacteria (P=0.007, P=0.007, and P=0.022, respectively). The level of Firmicutes was found to be significantly higher in mild FEV1 compared to moderate FEV1 (P=0.032), whereas the level of the other bacteria species was comparable across FEV1 severity groups. Conclusions: Our findings may encourage studies that target and modify gut microbiota to potentially achieve better outcomes in terms of respiratory function in CF.